Norovirus infection in immunocompromised children and children with hospital‐acquired acute gastroenteritis. Issue 7 (30th September 2013) - Munir, Naeemah; Liu, Pengbo; Gastañaduy, Paul; Montes, Julia; Shane, Andi; Moe, Christine
Abstract Norovirus (NoV) is a leading cause of acute viral gastroenteritis among children, yet its burden of disease among immunocompromised hosts and its role in hospital acquired infections (HAI) is not well characterized. To determine the prevalence, genotypes, and NoV loads among immunocompromised children and children with HAI, residual stool samples, and clinical data were collected at two major pediatric hospitals in metropolitan Atlanta from 92 children that were immunocompromised and/or had a hospital acquired acute gastroenteritis. NoV was identified in 16.3% (15/92) of all stool specimens; 23.4% (11/47) in immunocompromised only children, and 13.3% (4/30) in children with HAI. All NoV positive cases were genogroup II (GII), and GII.4 was the predominant strain followed by GII.3, GII.12, and GII.13. The average NoV load for immunocompromised patients was 6.3 ± 1.4 log genome equivalent copies (GEC) per gram of stool compared to 5.8 ± 1.1 log GEC among patients with HAI. NoV infections are common among immunocompromised children and children with hospital‐acquired gastroenteritis, underscoring the urgent need for rapid NoV detection system, and highlighting the importance of strict hospital hygiene practices. J. Med. Virol. 86:1203–1209, 2014. © 2013 Wiley Periodicals, Inc.